MicroRNA-105 inhibits human glioma cell malignancy by directly targeting SUZ12 - Jie Zhang; Weining Wu; Shuo Xu; Jian Zhang; Jiale Zhang; Qun Yu; Yuanyuan Jiao; Yingyi Wang; Ailin Lu; Yongping You; Junxia Zhang; Xiaoming Lu (Tumor Biology, 2017)
Glioma accounts for the majority of primary malignant brain tumors in adults and is highly aggressive. Although various therapeutic approaches have been applied, outcomes of glioma treatment remain poor. MicroRNAs are a class of small noncoding RNAs that function as regulators of gene expression. Accumulating evidence shows that microRNAs are associated with tumorigenesis and tumor progression. In this study, we found that miR-105 is significantly downregulated in glioma tissues and glioma cell lines. We identified suppressor of Zeste 12 homolog as a novel direct target of miR-105 and showed that suppressor of Zeste 12 homolog protein levels were inversely correlated with the levels of miR-105 expression in clinical specimens. Overexpression of miR-105 inhibited cell proliferation, tumorigenesis, migration, invasion, and drug sensitivity, whereas overexpression of suppressor of Zeste 12 homolog antagonized the tumor-suppressive functions of miR-105. Taken together, our results indicate that miR-105 plays a significant role in tumor behavior and malignant progression, which may provide a novel therapeutic strategy for the treatment of glioma and other cancers.